ANALYSIS OF ANISOTRPHY PARAMETERS WITH RESERVOIR QUALITY AND SCALING FACTOR OF SANDSTONE RESERVOIR BASED ON CORE SAMPLE FIELD, KUTAI WELL-LOG DATA (CASE STUDY: SADEWA FIELD, KUTAI BASIN, EAST KALIMANTAN) - Sita Ambarsari, Dona
Advanced modeling and interpretation of seismic data, especially in deep sea exploration fields, requires more detailed analysis of anisotropy effect and its relationship to reservoir quality parameters. Recently, there is no further study about anisotropy analysis with reservoir quality parameters and scaling factor from measurements of two different types of data (core sample and sonic logs). Anisotropy study from measurements of two different types of data (core sample and sonic logs) conducted in Sadewa Field which is a deep sea exploration field located in the Kutai Basin. The main reservoir in this field is the Early Miocene sandstone reservoir deposited in the upper slope channel environment which have been proven contain hydrocarabon. The study used two types of data, core sample data and sonic log data from two wells (DSA-4 and DSA-5ST1). A total of 25 rock core samples were taken at measured depth around 3000 – 4000 m. These core samples were measured for several analysis, such as thin section petrographic analysis, core analysis (porosity and permeability measurements) and ultrasonic velocity measurements. Ultrasonic velocity measurement for core sample, used a 1 MHz transducer to measure the velocity of Vp and Vs in the vertical and horizontal directions for the calculation of Thomsen's anisotropy parameters. Meanwhile, dipole sonic log data 10-40 KHz from both wells, at the same core sample depth position are used to obtain elastic parameters (Vp, Vs, Poisson ratio, etc.) and Thomsen's anisotropy parameters. Anisotropy analysis on core sample and log data shows that there is a linear relationship between anisotropy parameters and reservoir quality parameters. Those linear relationships are divided into two separate clusters based on rock quality. Cluster separation analysis using the critical porosity model shows that sampels with good quality are associated with high critical porosity values (> 0.257). The dominant factor that influences anisotropy is the presence of porosity in the form of a hydrocarbon interlayer which is formed when the sediment undergoes mesodiagenesis or burial diagenesis, which the sediment was buried to greater than about 2000 m or was buried to depths where the sediment is greater than 60 - 70?C. Fractures and intercalation (in the form of siltstone lenses) do not play a dominant role in the increase in anisotropy values because their presence isiv in a low anisotropy trend. The presence of a hydrocarbon interlayer significantly increases the anisotropy value due to hydrocarbon layering which indirectly improves reservoir quality (permeability and porosity values). Scaling factors using anisotropy parameters from core sample and log data can be used on samples with dominant intergranular porosity or on samples with relatively low anisotropy (in this case with an average of ? = 0.14 and an average of ? = 0.13). The results of this research indicate that the quality of the reservoir rock significantly influences the magnitude of the anisotropy parameter both at the scale of core sample data and well log data.